Spanish version of the Actinic Keratosis Quality of Life questionnaire. (27th February 2017) - Alarcon, I.; Vinding, G.R.; Christensen, K.B.; Esmann, S.; Malvehy, J.; Puig, S.; Jemec, G.B.E.
Abstract: Background: Patient‐reported outcome measures are very important outcomes. For specific diseases, health‐related quality of life‐instruments (HRQoL) are increasingly used to provide data on patients' overall perceptions of the course of a given disease. Actinic keratoses (AKs) are common keratotic lesions that occur on chronically sunlight‐exposed skin. Only few studies regarding HRQoL in AKs have been made. Objective: In order to be able to compare HRQoL among different countries and cultures, we aimed to translate and validate the Actinic Keratosis Quality of Life (AKQoL) questionnaire into Spanish and quantify the impairment caused by AKs in Spanish patients. Methods: The AKQoL was translated. Then, 15 patients with AKs were interviewed to ensure cultural adaption before it was tested in one hundred patients with AK lesions at the Melanoma Unit of Hospital Clinic in Barcelona. Results: Validation showed high interitem correlations, as well as a high correlation of each item and the total score. Internal consistency (Cronbach's coefficient alpha) was also high at 0.91 and an alpha value of 0.90 at retest. The test–retest correlation was 0.96, and the intraclass coefficient was 0.98. Conclusion: The presented data support the AKQoL Spanish version as a valid and reliable HRQoL questionnaire for the description of AK‐related QoL and may provide a method for comparison of AK specific QoL between different cultures and countries.